1995
DOI: 10.1029/95gl00388
|View full text |Cite
|
Sign up to set email alerts
|

Results of decametric monitoring of the comet collision with Jupiter

Abstract: Decametric observations of Jupiter were made at frequencies from 16.7 to 32 MHz from the Maipu Radio Astronomy Observatory in Chile, the University of Florida Radio Observatory, and the Owens Valley Radio Observatory in California before, during, and after the collision of comet Shoemaker‐Levy 9 with the planet. No significant change in the general level of Jovian decametric activity that might be attributed to the comet was observed. However, single bursts of possibly Jovian origin appeared at two of the 12 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…It is quite interest that the Maeda et al's data still show a systematic results indicating the Jovian source when we take long integration time with running average of 1 minute. Carr et al (1995) have reported that the observations of the Jovian decameter wave radiation had been made covering the periods of Jovian magnetosphere passages of SL-9 fragments; the observations were made at Maipu Radio Astronomy Observatory of the University of Chile, the University of Florida Radio Observatory, and the Owen Valley Radio Observatory of the California Institute of Technology. About 11 frequencies were monitored ranging from 16.7 to 32 MHz; but observations were met interference problems (Can et al, 1994).…”
Section: Why the Other Stations Did Not Report?mentioning
confidence: 99%
“…It is quite interest that the Maeda et al's data still show a systematic results indicating the Jovian source when we take long integration time with running average of 1 minute. Carr et al (1995) have reported that the observations of the Jovian decameter wave radiation had been made covering the periods of Jovian magnetosphere passages of SL-9 fragments; the observations were made at Maipu Radio Astronomy Observatory of the University of Chile, the University of Florida Radio Observatory, and the Owen Valley Radio Observatory of the California Institute of Technology. About 11 frequencies were monitored ranging from 16.7 to 32 MHz; but observations were met interference problems (Can et al, 1994).…”
Section: Why the Other Stations Did Not Report?mentioning
confidence: 99%
“…The lo plasma torus is one of the source regions of the KOM radiation, and this is consistent with our results. On the other hand, Carr et al (1995) concluded from ground-based monitoring observations that there was no significant change in the Jovian decametric emission activity before, during, and after the impact period. This is consistent with our results, "The turbulence in the Jovian outer magnetosphere was weak.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is consistent with no significant change of the DAM radiation monitored on the ground (cf. Carr et al, 1995).…”
Section: Discussionmentioning
confidence: 99%